(3OjhGf GdeTYTYjs - (3Ydj Hf Nda Hf YHO GdeWdH Hf MjOQ Hf eMeO Hf adGM GdehShj GdMhjRj GdeTYTYj,J (B1087 (3g` s
(3ChdgG (B:s
(3bGd eJhSdkG Edi Gddg JYGdi HGdfHj hBdg Ydjge GdUdGI hGdUdGe Edgj jGPG GdLhO hGdeLO hGdYdG hjG UGMH GdCaVGd hGdef hGdYWG s
(3BNQgG (B:s
(3hNjQ UdGI Gddg eGPQ TGQb Ydi GdeUWai hGdBd JHOj hJYbH s
(3GfXQgG eY OjhGf GdcYHjs
(3fSNI KGfjIGdeDda cGf MjkG SfI (B1087(3g``s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B208 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs